2002
DOI: 10.1023/a:1014900600815
|View full text |Cite
|
Sign up to set email alerts
|

Staging of Breast Cancer: New Recommended Standard Procedure

Abstract: The standard staging procedures to detect metastatic disease at breast cancer diagnosis require modification. On the basis of the literature data and our findings, the full staging procedure is appropriate in the second group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 15 publications
2
56
0
7
Order By: Relevance
“…The presence of distant metastases, outside the breast and regional nodes, is an important factor predicting prognosis and directing the intensity of care, because metastatic (stage IV) breast cancer has a low likelihood of cure. Because of the low yield, cost, and distress associated with investigating detected abnormalities that are-for the most part-falsepositives, baseline systemic staging is neither performed nor recommended (54) before surgery and axillary staging in patients with early-stage breast cancer (56,98,99). In the patients with more advanced disease (such as LABC or inflammatory breast cancer), however, some evidence supports the use of systemic imaging staging at the diagnosis to rule out stage IV disease, which would significantly alter treatment options because of the high likelihood of distant metastases (30,100).…”
Section: Distant (Systemic) Stagingmentioning
confidence: 99%
“…The presence of distant metastases, outside the breast and regional nodes, is an important factor predicting prognosis and directing the intensity of care, because metastatic (stage IV) breast cancer has a low likelihood of cure. Because of the low yield, cost, and distress associated with investigating detected abnormalities that are-for the most part-falsepositives, baseline systemic staging is neither performed nor recommended (54) before surgery and axillary staging in patients with early-stage breast cancer (56,98,99). In the patients with more advanced disease (such as LABC or inflammatory breast cancer), however, some evidence supports the use of systemic imaging staging at the diagnosis to rule out stage IV disease, which would significantly alter treatment options because of the high likelihood of distant metastases (30,100).…”
Section: Distant (Systemic) Stagingmentioning
confidence: 99%
“…On the contrary, several studies reported a limited value of breast cancer baseline staging, suggesting that complete diagnostic workup should be limited to patients with higher pre-test probability of distant metastases. 6,15,16 In particular, it has been shown that the prevalence of detectable metastatic disease in newly diagnosed breast cancer patients is exceedingly low and increases from stage I to stage III. 15,16 LUS detected liver metastasis very rarely in pathological stage I-II disease and approximately 2-3% in stage III disease.…”
Section: Discussionmentioning
confidence: 99%
“…6,15,16 In particular, it has been shown that the prevalence of detectable metastatic disease in newly diagnosed breast cancer patients is exceedingly low and increases from stage I to stage III. 15,16 LUS detected liver metastasis very rarely in pathological stage I-II disease and approximately 2-3% in stage III disease. 17,18 Chest x-ray has the lowest detection rate of all staging investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additonally, the National Comprehensive Cancer Network (NCCN) guidelines recommended the use of imaging only in cases with locally advanced disease or signs/symptoms that are suggestive of distant metastases (1). Notably, approximately 4% of breast cancer patients have detectable metastatic disease at the time of primary diagnosis and the majority of these patients exhibit symptoms of metastasis (2). However, if primary surgical treatment is performed after overlooking occult metastases in an asymptomatic patient, the delay in beginning systemic pharmacotherapy may affect the prognosis.…”
Section: Introductionmentioning
confidence: 99%